Identifying promising GSK3β inhibitors for cancer management: a computational pipeline combining virtual screening and molecular dynamics simulations - Hua, Libo; Anjum, Farah; Shafie, Alaa; Ashour, Amal Adnan; Almalki, Abdulraheem Ali; Alqarni, Ali Abdullah; Banjer, Hamsa Jameel; Almaghrabi, Sarah Abdullah; He, Shan; Xu, Nenggui (Frontiers in Chemistry, 2023)
Glycogen synthase kinase-3 (GSK3β), a serine/threonine protein kinase, has been discovered as a novel target for anticancer drugs. Although GSK3β is involved in multiple pathways linked to the etiology of various cancers, no specific GSK3β inhibitor has been authorized for cancer therapy. Most of its inhibitors have toxicity effects therefore, there is a need to develop safe and more potent inhibitors. In this study, a library of 4,222 anti-cancer compounds underwent rigorous computational screening to identify potential candidates for targeting the binding pocket of GSK3β. The screening process involved various stages, including docking-based virtual screening, physicochemical and ADMET analysis, and molecular dynamics simulations. Ultimately, two hit compounds, BMS-754807 and GSK429286A, were identified as having high binding affinities to GSK3β. BMS-754807 and GSK429286A exhibited binding affinities of −11.9, and −9.8 kcal/mol, respectively, which were greater than that of the positive control (−7.6 kcal/mol). Further, molecular dynamics simulations for 100 ns were employed to optimize the interaction between the compounds and GSK3β, and the simulations demonstrated that the interaction was stable and consistent throughout the study. These hits were also anticipated to have good drug-like properties. Finally, this study suggests that BMS-754807 and GSK429286A may undergo experimental validation to evaluate their potential as cancer treatments in clinical settings.